Model Evaluasi CIPP pada Program Pemberantasan Sarang Nyamuk Demam Berdarah Dengue - Ismayanti, Galuh (Jurnal Kesmas Asclepius, 2025)
This study aims to determine the extent to which the implementation of the PSN program is in accordance with the planned objectives and whether the program can control the breeding of mosquito larvae so that it can reduce the number of DHF cases. This study uses a qualitative method with a descriptive analytical approach. The CIPP evaluation model is used to evaluate the context, input, process, and product to determine the success of the PSN program. Information was obtained from twelve informants recruited by purposive sampling. The results of the research data were collected in the form of interviews, observations, and document reviews to evaluate the Dengue Fever Mosquito Nest Eradication (PSN) program in Palembang City in 2022. In general, the PSN program has been running well but is still constrained by the budget. In addition, there is no SOP related to mosquito nest eradication and community participation is still lacking. The conclusion of this study is that the Palembang City Health Office uses the results of this study as a basis for determining budget allocations for mosquito nest eradication programs and compiling SOPs for mosquito nest eradication to facilitate the implementation of the program, by increasing coordination, participation, and community empowerment to carry out village competitions free of mosquito larvae and provide awards for villages that have been declared free of mosquito larvae by the Health Center to encourage community participation in mosquito nest eradication. Keywords: Aedes Mosquito, CIPP Evaluation, Dengue Hemorrhagic Fever, PSN.